New material for ducting in air-conditioning system / Sulaiman Kamari and Wan Shukri Mohamad - Kamari, Sulaiman; Mohamad, Wan Shukri (1997)
Koolduct LTD presents this specification as a recommended method of fabricating and installing air ducting using foam panels and the Koolduct system as detailed herein. Koolduct makes no warranty, expressed or implied, regarding merchant ability or fitness for any particular installation. This specification is protected by copyright law, and the unauthorised reproduction, or any portion of it, is punishable by law. The Heating, Ventilation, and Air-Conditioning (HVAC) industry is in the midst of a dynamic era. However, air ducting, a critical component of HVAC system, has remained virtually unchanged since the early 1900's. Several factors and recent innovations have introduced the need to revolutionise air ducting. Building materials and insulating products have dramatically improved. Requirements for clean air are becoming increasingly stringent. Energy costs have continued to escalate. Changing fire and smoke codes have raised the standards for compliance. Finally, declining construction on a global basis has intensified competition, and accordingly, the search for an alternative technology.